2006
DOI: 10.1186/1745-6215-7-12
|View full text |Cite
|
Sign up to set email alerts
|

Duodenum preserving pancreatectomy in chronic pancreatitis: Design of a randomized controlled trial comparing two surgical techniques [ISRCTN50638764]

Abstract: The trial is conducted in compliance with the protocol and in accordance with the moral, ethical, regulatory and scientific principles governing clinical research as set out in the Declaration of Helsinki (1989) and the Good Clinical Practice guideline (GCP). The Center for Clinical Studies of the Department of Surgery Heidelberg is responsible for planning, conducting and final analysis of the trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…These findings were supported by another study by Andersen and Topazian [55]. An RCT is ongoing to compare this procedure with other forms of DPPHR (Beger and Frey), and the reports are awaited [56].…”
Section: Resectional Proceduressupporting
confidence: 62%
“…These findings were supported by another study by Andersen and Topazian [55]. An RCT is ongoing to compare this procedure with other forms of DPPHR (Beger and Frey), and the reports are awaited [56].…”
Section: Resectional Proceduressupporting
confidence: 62%
“…Some believe (minimal) resection should be part of any surgical procedure for CP, whereas others generally do not perform resection. 11,12 The argument against drainage without resection is that these patients would be insufficiently treated, leading to early recurrence of pain. On the contrary, another recent study suggested that patients selected for a PD drainage procedure have a better postoperative QoL than those undergoing resectional procedures.…”
mentioning
confidence: 99%
“…Subsequently, both the opened pancreatic and common bile ducts were included in the end-to-side anastomosis of the pancreatic head with an interposed jejunal loop [22]. The LPJ-a major part of the Frey procedure-was omitted [22][23][24].…”
Section: Pancreatic Operationsmentioning
confidence: 99%
“…The Bern modification of DPPHR is used to try to combine the advantages of the Beger and Frey/Smith procedures and consists of a central pancreatic head resection without transsection of the pancreas, whereas the LPJ-a major part of the Frey procedure-is omitted [22][23][24].…”
mentioning
confidence: 99%